Impact of Local Congruences in Attribute Reduction - Aragón, Roberto G. (Information Processing and Management of Uncertainty in Knowledge-Based Systems, 2020)
Local congruences are equivalence relations whose equivalence classes are convex sublattices of the original lattice. In this paper, we present a study that relates local congruences to attribute reduction in FCA. Specifically, we will analyze the impact in the context of the use of local congruences, when they are used for complementing an attribute reduction.